On regular variation of entire Dirichlet series - P. V. Filevych; O. B. Hrybel (Математичні Студії)
Consider an entire (absolutely convergent in $\mathbb{C}$) Dirichlet series $F$ with the exponents $\lambda_n$, i.e., of the form $F(s)=\sum_{n=0}^\infty a_ne^{s\lambda_n}$, and, for all $\sigma\in\mathbb{R}$, put $\mu(\sigma,F)=\max\{|a_n|e^{\sigma\lambda_n}:n\ge0\}$ and $M(\sigma,F)=\sup\{|F(s)|:\operatorname{Re}s=\sigma\}$. Previously, the first of the authors and M.M.~Sheremeta proved that if $\omega(\lambda)<C(\rho)$, then the regular variation of the function $\ln\mu(\sigma,F)$ with index $\rho$ implies the regular variation of the function $\ln M(\sigma,F)$ with index $\rho$, and constructed examples of entire Dirichlet series $F$, for which $\ln\mu(\sigma,F)$ is a regularly varying function with index $\rho$, and $\ln M(\sigma,F)$ is not a regularly varying function with index $\rho$. For the exponents of the constructed series we have $\lambda_n=\ln\ln n$ for all $n\ge n_0$ in the case $\rho=1$, and $\lambda_n\sim(\ln n)^{(\rho-1)/\rho}$ as $n\to\infty$ in the case $\rho>1$. In the present article we prove that the exponents of entire Dirichlet series with the same property can form an arbitrary sequence $\lambda=(\lambda_n)_{n=0}^\infty$ not satisfying $\omega(\lambda)<C(\rho)$. More precisely, if $\omega(\lambda)\ge C(\rho)$, then there exists a regularly varying function $\Phi(\sigma)$ with index $\rho$ such that, for an arbitrary positive function $l(\sigma)$ on $[a,+\infty)$, there exists an entire Dirichlet series $F$ with the exponents $\lambda_n$, for which $\ln \mu(\sigma, F)\sim\Phi(\sigma)$ as $\sigma\to+\infty$ and $M(\sigma,F)\ge l(\sigma)$ for all $\sigma\ge\sigma_0$.